Modeling and control of double star induction machine by active disturbance rejection control - Aichetoune Oumar; Rachid Chakib; Mohamed Cherkaoui (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper aims to contribute to the modeling and control of the double star induction machine (DSIM) by a robust method called active disturbance rejection control (ADRC). The ADRC has become in the last decade one of the most important techniques of regulation. This method is based on the use of an ESO (Extended State Observer) which estimates in real-time and at the same time the external disturbances and the errors due to the variations of the parameters of the machine and to the uncertainties of modeling. The two stators of DSIM are powered by three-phase inverters based on transistors and MLI control and the entire system is modeled in Park's reference. We analyze in the Matlab/Simulink environment the dynamic behavior of the system and the different ADRC controllers under different operating conditions. The result has demonstrated the performance and effectiveness of the ADRC.